Antihypertensive drugs and the risk of incident rosacea3. (6th July 2014) - Spoendlin, J.; Voegel, J.J.; Jick, S.S.; Meier, C.R.
Summary Background Despite scarce evidence, use of calcium channel blockers is discouraged in patients with rosacea, whereas beta‐blockers are recommended as an off‐label treatment for erythematotelangiectatic rosacea. Objectives To study the association of the use of calcium channel blockers, beta‐blockers and other antihypertensive drugs with incident rosacea. Methods We conducted a matched case–control study of antihypertensive drugs and incident rosacea, using the U.K.‐based General Practice Research Database. Cases had an incident diagnosis of rosacea recorded between 1995 and 2009. Each case was matched to one control on age, sex, general practice and years of history on the database before the index date. Drug use was stratified by timing (≤ or > 180 days before the index date) and duration (number of prescriptions) of drug exposure, in a multivariate conditional logistic regression model. Results Among 53 927 cases and 53 927 controls, we observed odds ratios (ORs) around unity for calcium channel blockers across all strata, with a slightly decreased OR of 0·77 (95% CI 0·69–0·86) for current users of dihydropyridine calcium channel blockers with ≥ 40 prescriptions. Among beta‐blockers, atenolol and bisoprolol yielded slightly decreased ORs across all exposure strata, whereas propranolol revealed ORs around 1·0, irrespective of timing and duration of exposure. Neither angiotensin‐converting‐enzyme inhibitors nor angiotensin receptor blockers altered the relative rosacea risk. Conclusions Our data contradict the prevailing notion that calcium channel blockers increase the risk of rosacea. Beta‐blocker use was associated with a slightly decreased risk of rosacea, but the effect may be somewhat stronger in patients with erythematotelangiectatic rosacea.